Mathematical model of filtration under conditions of variable porosity taking into account biocolmatage - Natalia, Ivanchuk; Petro, Martyniuk; Olga, Michuta (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
The authors' research concerns the equations of filtration in soils taking into account the growth of microorganisms. A review of works, statement of research problems and a mathematical model of filtration of an organic substances solution, taking into account the effect of biocolmatage was conducted.